Pengaruh Pengetahuan Perpajakan dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak UMKM Di Jakarta - Saprudin saprudin; Riyanto Wujarso; Rina Dameria Napitupulu (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2020)
Indonesia's national development is mostly financed by state revenues from the tax sector, so that taxpayer compliance in fulfilling their tax obligations is very important. On the other hand, the growth of micro, small and medium enterprises is quite rapid so they need attention and guidance so that they become obedient taxpayers. This study focuses on seeing how the influence of knowledge of taxation and tax sanctions on taxpayer compliance of small and medium micro business actors in the Special Capital Region of Jakarta. This research was conducted by distributing questionnaires to MSME business actors who met the criteria, while the sample was taken randomly. From the 60 respondents of MSME business actors who were obtained by researchers, then the data was carried out by various data tests such as validity and reliability tests before processing the data through classical assumption tests and regression tests with the help of SPSS. The results of this study indicate that tax knowledge has an effect on taxpayer compliance, tax sanctions also have a significant effect on taxpayer compliance. Likewise, knowledge of taxation and tax sanctions together has a significant effect on taxpayer compliance of micro, small and medium enterprises. Thus, according to researchers, the government and other related parties need to provide a lot of socialization and tax training to MSME business actors, this is also because it is suspected that many new MSME business actors do not really understand the tax provisions for their business. So it is hoped that the mandatory tax compliance of MSME actors will increase and in the end will also increase state revenues to finance development.